SUPERSIMETRÍA EN MECÁNICA CUÁNTICA. - Villegas Silva, Fulgencio (2004)
Using ideas about supersymmetry applied to Quantum Mechanics; it is shown how to obtain wave functions and energy spectra tor a Hamiltonian series using a method which involves creation and annihilation operators, similar to the ones used for the hannonic oscillator. The integrability condition, named fonn invariance, is tested and it is necessary in order to reproduce the original total spectrum. Two examples that help to visualize the method are shown.